The Grammatical Structure of Limericks in English: an Analytical Examination - Seytjanov, Jetker; Dilnoza, Jaksulikova; Nursuliu, Kokanova (European Journal of Life Safety and Stability (2660-9630), 2023)
Limericks, a popular form of poetry characterized by their witty and playful nature, possess a unique grammatical structure that contributes to their distinctiveness. This scientific article aims to analyze the grammatical features and patterns found within English limericks, shedding light on their syntactic organization, linguistic constraints, and creative potential. By examining a diverse collection of limericks and employing linguistic theories, this study provides a comprehensive exploration of the grammatical structure underlying these humorous verses.